USING TEMBELEK (LANTANA CAMARA) PLANTS AS THE BASIC MATERIALOF MOSQUITO REPELLENT LOTION - Nani Rahmah; Maisel Priskilla S.; Deni Aryati; Dwi Handayani; Tri H. (Pelita - Jurnal Penelitian Mahasiswa UNY, 2013)
The aims of the research were (1) to find out whether tembelek (lantana camara)plants could be used as the basic material of mosquito repellent lotion; (2) to findput how to make mosquito repellent lotion from tembelek (lantana camara) plants;and (3) to find out whether the mosquito repellent lotion made of tembelek (lantanacamara) plants were safe for the skin.The research method was an experimental one. The research was conducted atSamirono CT IV/160, analysis chemistry laboratory of Ahmad Dahlan University, danlaboratorium Chemix Bantul for five months. The subjects were various kinds of mosquitosand the objects of the research were the tembelek (Lantana camara) plants. Thesteps in this research were (1) observing; (2) experimenting the making of mosquitorepellent lotion; and (3) testing the product.The findings showed that Lantana camara could be used as the material ofmaking the lotion. Three types of lotion were produced with different levels of extracts,namely 10%, 20%, and 30% to get the best formula. Based on the result of theorganoleptic and effectiveness tests in repelling mosquitos, it was found out that thelotion with the extract level of 20% proved to be good in terms of color, smell, texture,safety for the skin and effectiveness in repelling mosquitos.